The effect of field of view of a camera on enhancing the immersive feeling of the audience in a networked dance performance - Hee Soh, Joong; Ji Kim, Hye; Goo, Boncheol (Revista Eletrônica MAPA D2 - Mapa e Programa de Artes em Dança (e Performance) Digital, 2015)
Representation of lively telepresence via video has been one of the most significant tasks of networked dance performances. Different researchers have adopted different camera systems by using multiple 3D cameras, attaching cameras on a dancer’s body, or creating an augmented reality system. However, because these systems are either performer-centered or high-cost, more search for an effective camera control is necessary. This paper suggests controlling the field of view (FOV) of a single camera in various ways to represent more vivid telepresence. The user survey conducted implied that FOV alone can affect the immersive feeling of the audience. The result would be helpful for making a more effective use of a simple camera system in a networked dance performance.